Education Management Paradigm, Philosophy, and Policy - Ulfiani, Dwi Yulia; Maksum, Muh. Nur Rochim; Azani, Mohammad Zakki (Universitas Muhammadiyah Surakarta, 2023)
The implementation of the Merdeka curriculum is one of the efforts undertaken by SMA Al-Islam 1 Surakarta to address learning loss. The objective of this study is to explore the relationship between learning loss and the implementation of the Merdeka curriculum at SMA Al-Islam 1 Surakarta. A qualitative research method with a case study design was employed for this study. The research focuses on depicting the initiatives of SMA Al-Islam 1 Surakarta in implementing the Merdeka curriculum and assessing the effectiveness of the Merdeka curriculum in mitigating learning loss. The research findings indicate that students experience learning loss in the form of decreased learning motivation, declining academic performance, and the emergence of undesirable behaviors. However, the school can minimize these issues by implementing aspects of the Merdeka curriculum, such as project-based assessments and differentiated learning methods. These strategies aim to provide students with a sense of achievement and cater to their individual learning needs.